Analyses of Calcium-Independent Phospholipase A(2)beta (iPLA(2)β) in Biological Systems - Barbour, S.E. (Methods Enzymol, 2016)
The Ca(2+)-independent phospholipases A(2) (iPLA(2)s) are part of a diverse family of PLA(2)s, manifest activity in the absence of Ca(2+), are ubiquitous, and participate in a variety of biological processes. Among the iPLA(2)s, the cytosolic iPLA(2)β has received considerable attention and ongoing studies from various laboratories suggest that dysregulation of iPLA(2)β can have a profound impact on the onset and/or progression of many diseases (e.g., cardiovascular, neurological, metabolic, autoimmune). Therefore, appropriate approaches are warranted to gain a better understanding of the role of iPLA(2)β in vivo and its contribution to pathophysiology. Given that iPLA(2)β is very labile, its basal expression is low in a number of cell systems, and that crystal structure of iPLA(2)β is not yet available, careful and efficient protocols are needed to appropriately assess iPLA(2)β biochemistry, dynamics, and membrane association. Here, step-by-step details are provided to (a) measure iPLA(2)β-specific activity in cell lines or tissue preparations (using a simple radiolabel-based assay) and assess the impact of stimuli and inhibitors on resting- and disease-state iPLA(2)β activity, (b) purify the iPLA(2)β to near homogeneity (via sequential chromatography) from cell line or tissue preparations, enabling concentration of the enzyme for subsequent analyses (e.g., proteomics), and (c) employ hydrogen/deuterium exchange mass spectrometry analyses to probe both the structure of iPLA(2)β and dynamics of its association with the membranes, substrates, and inhibitors.